A pooled analysis of six large-pen feedlot studies: effects of a noncoated initial and terminal implant compared with a single initial and delayed-release implant on arrival in feedlot heifers. Issue 3 (2nd July 2020) - Smith, Zachary K; Renter, David G; Holland, Ben P; Word, Alyssa B; Crawford, Grant I; Nichols, Wade T; Nuttelman, Brandon L; Streeter, Marshall N; Walter, Lee-Anne J; Hutcheson, John P; Dicke, Bill; Brandt, Robert T; et al.
Abstract: Randomized complete block design experiments ( n = 6 experiments) evaluating steroidal implants (all from Merck Animal Health, Madison, NJ) were conducted in large-pen feedlot research facilities between 2015 and 2018 comparing an 80 mg trenbolone acetate (TBA) and 8 mg estradiol-17β (E2 ) initial implant (Revalor-IH) and reimplanted with 200 mg TBA and 20 mg E2 (Revalor-200; REPEATED) to a single 80 mg TBA and 8 mg E2 uncoated; 120 mg TBA and 12 mg E2 coated implant (Revalor-XH) at arrival (SINGLE) on growth and carcass responses in finishing heifers. Experiments occurred in Nebraska, Oklahoma, Washington, and Texas. Similar arrival processing was used across experiments where 17, 675 heifers [initial body weight = 333 kg SEM (4.1)] were enrolled into 180 pens (90 pens per treatment with 65–240 heifers per pen) and fed for 145–222 d. Only REPEATED heifers were removed from their pen at reimplant. Diets contained monensin and tylosin, consisted of ingredients common to each region, and contained greater than 90% concentrate. Ractopamine hydrochloride was fed for a minimum of 28 d prior to harvest. Linear mixed models were used for all analyses; model-adjusted means for each implant group and the corresponding SEM were generated. Distributions of U.S. Department of Agriculture (USDA) quality grade (QG) and yield grade (YG) were analyzed as ordinal outcomes. No differences ( P ≥ 0.11) were detected for any performance parameters except dry matter intake (DMI), where SINGLE had greater ( P = 0.02) DMI (9.48 vs. 9.38 ± 0.127 kg) compared with REPEATED. Heifers implanted with REPEATED had greater ( P ≤ 0.02) hot carcass weight (HCW; 384 vs. 382 ± 2.8 kg), dressing percentage (64.54 vs. 64.22 ± 0.120%), and ribeye area (91.87 vs. 89.55 ± 0.839 cm 2 ) but less ( P ≤ 0.01) rib fat (1.78 vs. 1.83 ± 0.025 cm) and calculated YG (2.82 vs. 2.97 ± 0.040) and similar ( P = 0.74) marbling scores (503 vs. 505 ± 5.2) compared with SINGLE heifers. Distributions of USDA YG and QG were impacted ( P ≤ 0.03) by treatment such that REPEATED had fewer USDA Prime and YG 4 and 5 carcasses. Heifer growth performance did not differ between implant regimens, but HCW and muscling did, perhaps indicating that REPEATED may be suited for grid-based marketing, and SINGLE might be suited for heifers sold on a live basis depending upon market conditions and value-based grid premiums and discounts. However, these decisions are operational dependent and also may be influenced by factors including animal and employee safety, stress on animals, processing facilities, time of year, labor availability, and marketing strategies.